Analysis Students’ Ability to Answer Higher Order Thinking Skills Questions on Reading Test of Narrative Text in Multiple Choice Form - One Laila Trisanti; Septiana, Tri Ilma; Sofiyatul Padillah (Universitas Pendidikan Ganesha, 2022)
The multiple-choice test is familiar to Foreign English Language Learners (EFL) and is able to measure students' HOTS especially in Indonesia. Although it has a number of limitations, multiple choice is widely used because it is able to measure learning outcomes from the simple to the complex. The aim of this study was to analyze the students' ability to answer Higher Order Thinking Skills (HOTS)-oriented questions in a multiple-choice form. In collecting data, the researchers used a narrative reading test of questions that had been carefully developed by the English teacher with a focus on the top three HOTS domains (e.g., analyzing, evaluating, and creating) and interviews with two students who were taken from upper and lower group. his study employed descriptive qualitative method. Moreover, the data obtained were sorted verified, analyzed, interpreted, drawn conclusions, and presented descriptively-qualitatively. The findings of this study indicated that there was not a single student in the excellent category (0%), 11 students in the good category (37%), 3 students in the fair category (10%), 6 students in the poor category (20%), and 10 students in the very poor category (33%). In addition, based on analysis of students’ answer errors, it was known that the percentage of students’ answer errors on the HOTS-oriented questions was analyzing 25%, evaluating 39%, and creating 36%. This indicated that some ninth-grade students at MTs Satu Atap Tangerang who have not been able to answer the HOTS oriented questions correctly.